ISCHEMIC STROKE IN A PATIENT WITH SYSTEMIC LUPUS ERYTHEMATOSUS AND SECONDARY ANTIPHOSPHOLIPID SYNDROME - P. S. Nikitenko; S. A. Goryacheva; S. V. Nikitenko; S. D. Dmitrienko; D. S. Sobko (SINAPS LLC, 2019)
The article presents a clinical case of an onset of antiphospholipid syndrome in a patient with systemic lupus erythematosus and ischemic stroke. Systemic lupus erythematosus is a non-modifiable risk factor for ischemic stroke.